Estrategias innovadoras aplicadas al proceso de enseñanza-aprendizaje en la asignatura de Lengua y Literatura de séptimo año de E.G.B. año lectivo 2022 - Toapanta Cando, Franklin Arturo (2023)
This project had the objective of demonstrating the teaching-learning process of Elementary Language and Literature, through the use of innovative strategies with digital and technological tools in the students of the seventh year of Basic General Education of the Educational Unit "Once de Noviembre" of the school year 2022, for which the relevant digital and technological tools were listed, it was determined how ICTs intervene in teaching through their use, the approach used in this process was quantitative, in addition the inductive method, a practical workshop was held with teachers to enhance the learning of Language and Literature in students, a survey was applied to four teachers and sixty-four students.